Kajian Pelaksanaan Continous Monitoring dan Continous Audit Terhadap Keberhasilan Pengelolaan Pengadaan Barang dan Jasa - Pakasi, Novrabella Clarashinta; Waani, Zigma Robert (Gorontalo Accounting Journal, 2023)
This paper will examine the implementation of continuous monitoring and continuous audit on the success of the management of procurement of goods and services in the local government agencies of North Sulawesi Province. The research was conducted at the Regional Inspectorate of North Sulawesi Province. The essence of this paper aims to determine the implementation of continuous monitoring and continuous audit on the success of the management of procurement of goods and services in the local government agencies of North Sulawesi Province. The data analysis techniques used are data reduction, data display, and conclusion drawing/verification which are carried out interactively and continuously until completion, so that the data becomes saturated. The results of this study show that: 1) Continuous monitoring by the APIP Inspectorate in the implementation of procurement of goods and services in the local government agencies of North Sulawesi Province has been carried out quite well. APIP conducts continuous monitoring to detect early on procurement that does not comply with the applicable regulations, thus APIP can immediately provide improvement suggestions to the local government agencies. 2) Continuous audit by the APIP Inspectorate in the implementation of procurement of goods and services in the local government agencies of North Sulawesi Province has been carried out quite well. APIP conducts continuous audits on strategic packages in local government agencies, so that if any fraudulent activities are found in the implementation of procurement, APIP can provide recommendations for immediate action by the local government agencies.